WHEN THE EARTH SHOOK AND MEANINGS SHIFTED: THE 1867 YOGYAKARTA EARTHQUEKE IN JAVANESE COSMOLOGY: Ketika Tanah Berguncang dan Makna Bergeser: Gempa Bumi Yogyakarta 1867 dalam Kosmologi Jawa - Eka Yudha Wibowo; sinta permata (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The 1867 Yogyakarta earthquake was one of the most destructive earthquakes on the island of Java in the 19th century, causing significant impacts not only in physical terms but also socially and culturally. This study aims to analyze the 1867 Yogyakarta earthquake as a socio-cultural event, the post-earthquake changes to the Tugu Golong Gilig monument, and its significance from a Javanese cosmological perspective.This study employs a historical method with a qualitative approach through the stages of heuristics, source criticism, interpretation, and historiography. Research sources include colonial archives, Dutch East Indies government reports, contemporary newspapers, and supporting literature.The findings indicate that the 1867 earthquake was understood as a sign of the disruption of cosmic balance in the Javanese people’s view. The collapse of the Golong Gilig Monument was interpreted as a symbol of the disruption of harmony between the king, the people, and nature. The change in the monument’s form following the earthquake represented an effort to restore that balance.These findings indicate that natural disasters in the Javanese context are not merely understood as physical phenomena but also as symbolic events tied to the community’s cosmology.